Holub R. C. Nietzsche and the Women’s Question / trans. from Engl. R. L. Kochnev - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
The article discusses collections of scientific papers edited by Paul Patton and Peter Burgard on the subject of the philosophy of Friedrich Nietzsche and modern ideas of the feminist tradition. Both collections contain debates about the ambiguity of the heritage of the German thinker in ethical and political thought. This review provides an analysis of the articles and approaches they use. The author criticized the tendencies to simplify Nietzsche’s philosophy